Transcriptomics of Biostimulation of Plants Under Abiotic Stress - González-Morales, Susana; Solís-Gaona, Susana; Valdés-Caballero, Marin Virgilio; Juárez-Maldonado, Antonio; Loredo-Treviño, Araceli; Benavides-Mendoza, Adalberto (Frontiers in Genetics, 2021)
Plant biostimulants are compounds, living organisms, or their constituent parts that alter plant development programs. The impact of biostimulants is manifested in several ways: via morphological, physiological, biochemical, epigenomic, proteomic, and transcriptomic changes. For each of these, a response and alteration occur, and these alterations in turn improve metabolic and adaptive performance in the environment. A large number of studies have been conducted on the effects of different biotic and abiotic stimulants on plants, including many crop species. However, as far as we know, there are no reviews available that describe the impact of biostimulants for a specific field such as transcriptomics, which is the objective of this review. For the commercial registration process of products for agricultural use, it is necessary to distinguish the specific impact of biostimulants from that of other legal categories of products used in agriculture, such as fertilizers and plant hormones. For the chemical or biological classification of biostimulants, the classification is seen as a complex issue, given the great diversity of compounds and organisms that cause biostimulation. However, with an approach focused on the impact on a particular field such as transcriptomics, it is perhaps possible to obtain a criterion that allows biostimulants to be grouped considering their effects on living systems, as well as the overlap of the impact on metabolism, physiology, and morphology occurring between fertilizers, hormones, and biostimulants.